Procedimiento para la cuantificación de los factores sísmicos de desempeño de estructuras diseñadas a partir de muros de cortante construidas en guadua laminada (2017)
The methodology presented at FEMA P-695 expose the behavior during collapse of structural systems of seismic resistance. This Methodology is complex, needs deep knowledge in advanced analysis of structures and extensive data management. This is why the present investigation includes the evaluation of structures designed from shear walls constructed with laminated bamboo, in order to build a manual and the handling computational modules for engineers with different levels of management in the methodology. This manual provides the necessary information for the creation of archetypes from a system of walls from laminated bamboo, the procedure for structuring of the performance groups, the creation of structural models with the SAWS software, made analysis models, and performance evaluation through a Matlab...